A theoretical investigation of convective patterns in the lee of the Colorado Rockies - Dirks, Richard A., author; Reiter, Elmar R., advisor; Grant, Lewis, committee member; Gray, William, committee member; Morel-Seytoux, Hubert, committee member (Colorado State University. Libraries, 1970)
The western Great Plains are observed to be the formation region for many of the summer convective systems in the central United States. Convective activity is greatly reduced in the immediate lee of the Colorado and New Mexico Rockies while it is intensified about a hundred kilometers eastward. An explanation of these observed convective patterns is proposed on the basis of a regional scale Rocky Mountains-Great Plains circulation system. A two-dimensional numerical model of a large scale mountain-plain circulation is presented which includes the effect of a slightly sloping plain. The equations are integrated over periods of two to eight hours for various initial conditions of thermal stability and ambient wind. An increase in thermal stability is found to suppress the developing circulation while the circulation is enhanced by an ambient shearing wind. Typical observed stability and ambient wind fields yield an interacting two cell circulation with a strong cell over the mountain slope and a weaker cell over the plain. The resulting airflow is characterized by strong descent (m sec -1) in the immediate lee of the mountains and weak ascent (cm sec -1) in a broad region 100 to 300 km leeward. An investigation of contributing factors reveals the effect of the plain slope to be a primary cause of the ascending flow over the plain. The flow patterns which develop correspond well with observed diurnal oscillations in upper wind profiles over the plains with regard to velocity magnitude, time of reversal, and depth of flow. The dynamic effects of the circulation are found to be of sufficient magnitude to control convective activity. The spatial distribution of the dynamic effects is also in general agreement with observations of related convective activity. Nocturnal cooling reverses the circulation around "sunset" and results in ascending flow in the near lee of the mountains. This compares favorably with observed convective activity in that region. An examination of orographic waves and other plausible mechanisms finds that these are not generally applicable over the wide range of observed conditions. This restriction does not apply to the Rocky Mountains-Great Plains circulation system.
Keywords: Micrometeorology